Zmiany w doradztwie pedagogicznym dla nauczycieli religii na przełomie tysiącleci - Elżbieta Sozańska (Nicolaus Copernicus University in Toruń, 2008)
Changes in pedagogical consultancy for religion education teachers at the turn of the millennia   The article consists of five parts showing the pedagogical consultancy phenomenon and its evolution over the last fifty years. The first part analyses the idea of consultancy and its understanding. The second part discusses the situation of religion education teachers consultancy and the ways its execution under the regime of the socialist country. The third part contains the synthesis of advisory actions after 1989 in Poland. It shows a fast development of forms and methods of advisory actions and their effect on religion teachers who have become school teachers since 1990. The fourth part shows the evolution of consultancy on the grounds of one's own research. The last part determines the contemporary expectations for consultancy and the possibilities to meet them.